Government Bonds Yield In Indonesia: Econometric Analysis of Error Correction Model (ECM) Period 2010–2023 (Proceeding of the International Conference on Economics, Accounting, and Taxation, 2024)
This study aims to determine the effect of Economic Growth Rate, BI Rate , Inflation, Exchange Rate and Oil Price on Bond Yields, especially Government Bonds of the Republic of Indonesia for the period 2010-2023. The method used is a quantitative method with econometric analysis of Error Correction Model (ECM) regression. The data used in this study were obtained from statistical reports on the website of the Financial Services Authority of the Republic of Indonesia (OJK-RI), Bank Indonesia, the Central Statistics Agency and several related agencies. The results of the study indicate that economic growth and oil prices are negatively correlated but do not significantly affect bond yields in the long run. The variables of BI Rate and Exchange Rate are positively correlated and significantly affect bond yields. The variable of Inflation is positively correlated but does not significantly affect Bond Yields. While for the short term, partially the variables of BI Rate and Exchange Rate are positively correlated and significantly affect Bond Yields. The variables of inflation and oil price are positively correlated but do not significantly affect bond yields. The Economic Growth Rate variable is negatively correlated but does not have a significant effect on bond yields. Together, the independent variables consisting of Economic Growth Rate, BI Rate, Inflation, Exchange Rate, and Oil Prices have an effect on bond yields, both in the long term and the short term.